The system of sustainable development as a theoretical basis for training of the future ecologists - Боголюбов, В. М. (Scientific Progress & Innovations, 2015)
The article analyzes the main principles of sustainable development in the context of future environmentalists. In order to form professional competence of Master ecologist attention is focused on implementing a meaningful learning process competencies. These competencies are based on competency-active approach and taking into account the requirements of industry standards. For each discipline program for professional training we highlighted key and professional competence in the context of solving the problems of transition to sustainable development and the principles of well-adjusted use of natural resources.